The comovement and causality between stock market cycle and business cycle in China: Evidence from a wavelet analysis - Si, Deng-Kui; Liu, Xi-Hua; Kong, Xianli (Economic modelling, 2019)
This study aims to explore the comovement and causal relationship between the stock market cycle and business cycle in China over the period from 1992Q1 to 2018Q1. While the existing literature treats the relationship as being time- and/or frequency-invariant, we attempt to detect possible time- and frequency-varying patterns by using wavelet analysis. The results show that the stock market cycle tends to lead the business cycle in expansion periods whereas the business cycle tends to lead the stock market in recession periods. Moreover, when the stock market cycle leads the business cycle, they are always positively correlated. In contrast, when the business cycle leads the stock market cycle, they tend to be negatively correlated. In addition, we find that there are substantial time- and frequency-variations in the comovement and causal relationship between the two cycles in China, suggesting the presence of the time- and frequency-variation features should not be ignored in future research. Finally, the relationship can be significantly affected by the domestic interest rates as well as the effect of some external shocks, such as the interest rate and business cycle shocks originated from other major advanced countries. These findings shed new light on the literature that merely considers one specific subject of the relationship and ignores the time and frequency-varying natures in the relationship. •We assess how the comovement and causality between the two cycles vary across frequencies and change over time.•We do find substantial time- and frequency-variations in the considered relationships.•The stock market cycle tends to lead the business cycle in the short term.•The business cycle tends to lead the stock market cycle in the intermediate and long terms.•The stock market shows a differential cyclical behavior over economic expansion and recession periods.